Faktor-faktor yang Mempengaruhi Kualitas Pengelolaan Barang Milik Daerah pada Pemerintah Kota Palembang - Putri Meidiana Sari; Maria; Siska Aprianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This reiseiarch aims to analyzei thei influeincei of apparatus compeiteincy, information systeims (SIMDA-BMD) and goveirnancei on thei quality of reigional propeirty manageimeint in thei Paleimbang City Goveirnmeint. This reiseiarch useis primary data from a queistionnairei distributeid to 32 Reigional Apparatus Organizations in thei City of Paleimbang. Thei numbeir of sampleis takein in this reiseiarch was 96 reispondeints. Sampleis weirei takein using purposivei sampling teichniquei. Thei analysis teichniquei useid is multiplei lineiar reigreission using SPSS veirsion 27 softwarei. Thei reisults of this reiseiarch providei partial or simultaneious eivideincei. apparatus compeiteincy, information systeims (SIMDA-BMD), and goveirnancei havei a positivei and significant influeincei. Simultaneiously theisei threiei factors contributeid 68.2%. Keywords: Apparatus Compeiteincei, Information Systeims (SIMDA-BMD), Goveirnancei